Marketing científico digital: avaliação da visibilidade de periódicos em Ciência da Informação - Sarmento, Danielle dos Navegantes (2023)
The journal is the most used means of communication by the scientific community due to its relevance and possibility of measuring scientific impact. In the current context, social media has been established as a locus of communication and sharing, it is understood that the use of social media has become a strategic activity for promoting scientific visibility. It is an activity related to digital marketing applied to scientific work, aiming to promote products and services. The present research aims to analyze the visibility of scientific communication in open access Brazilian scientific journals in the area of Information Science, indexed in the Information Science Reference Database (BRAPCI). This research is quantitative and qualitative in nature and uses bibliographical research for theoretical basis, also characterizing itself as exploratory research in relation to its objectives. After refinement, the corpus of analysis consisted of 37 journals that have a Qualis/Capes stratum in the area of Communication and Information. To investigate digital marketing and open access policies, the use of media to promote periodicals and articles and the editors' perception of these directions, the following sources and data collection instrument were used: the periodical websites, the Dimensions Analytics tool and journal editors. After triangulating the results, the study was able to identify that promoting the visibility of scientific journals is carried out through national and international sources and indexing tools; open access policies and digital scientific marketing actions, which are largely promoted through social media. The existence of digital marketing actions and strategies was verified in all journals, but these practices are not structured, with only one digital scientific marketing plan being identified on the journal websites. Given these results, it is understood that for greater credibility and more assertive results in promoting the visibility of these journals and their scientific articles, it is necessary that all dissemination actions and strategies are planned and formalized through digital scientific marketing.